Search Engine Optimisation and Google Answer Box - Andrej Miklošík; Ferdinand Daňo (Communication Today, 2025)
Changing behaviour of users searching online is reflected by search engines that strive to provide best search results to retain the loyalty of their users and increase their market share. Google as the global market leader innovates its services constantly and works on improving the usability of its search results. Introducing Google Answer Boxes has changed the way Google presents information on the one side and the way how users search for the information on the other. For website owners it is vital being included in search results and even more being excerpted in the Google Answer Box. Here, the user can see much more content from the website and thus, the owner can build brand awareness and gain extra conversions as well. In this article, the authors aim at analysing the benefits and dislikes of Google Answer Boxes for three different groups: Users, Google and website owners. The authors analyse one of the Google Answer Box’s form deeper by using a case study. Results of primary research are further presented in the form of pointing out at strengths and weaknesses of this technology in application for different entities/audiences. The main objective of the text is to analyse differences in the frequency of the occurrence of Google Answer Boxes when searching for different phrases beginning with “How to”, “I want to buy” and “I want to do”. The empirical study includes 30 different search phrases in 4 languages, thus analysing 120 search results in total. The authors analyse the status quo regarding the appearance of Google Answer Box in any of its different forms for these types of search queries and identify differences in the frequency of Google Answer Box appearance in the Australian, German, Czech and Slovak version of Google.